THE ENCOURAGEMENT SYSTEM DESIGN UNMANNED AMPHIBIOUS VEHICLES - Aris Tri Ika Rakhmadi; Mochamad Yunus (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2021)
ABSTRACT Rupanpur is an Organic Unit of the Marine Corps Infantry Battalion which acts as the eyes and ears of the Battalion to provide intelligence data on the front situation of the battle to ensure the landing passage is safe from obstacles and enemies, so as to reduce the risk of casualties when Rupanpur is on duty, an Unmanned Amphibious Vehicle is needed. This tool is capable of operating both on land and at sea, and can be controlled remotely using a remote control. The Unmanned Amphibious Vehicle propulsion system consists of land and sea, for ground propulsion operations using a motor transmission system and sprockets, while for propulsion at sea using waterjet propulsion. From the calculation, the total resistance of the Unmanned Amphibious Vehicle is 16,628 N, so it requires a motor power of 33,25 watts or 0.04 HP with a speed of 2 m/second. As for the total resistance in water, the value is 5.52414 N, so it requires a Brushlees motor with a Shaft Horse Power (SHP) value of 24,2 watts. The results of the land and sea trials went well with a land speed of 2 m/second and a sea speed of 5 knots = 2,572 m/second. Keywords: Amphibious, Propulsion System, Waterjet